A Fast and Economical Sample Preparation Protocol for Interaction Proteomics Analysis. Issue 9 (18th April 2019) - Gonzalez‐Lozano, Miguel A.; Koopmans, Frank; Paliukhovich, Iryna; Smit, August B.; Li, Ka Wan
Abstract: A simple and fast immunoprecipitation (IP) protocol is designed with the sample preparation incorporated, applicable to both low and high throughput. This new protocol combines two procedures based on magnetic beads in 96‐well plate format. Protein complexes are captured by antibodies and magnetic beads conjugated with protein A. Proteins are washed and on‐bead digested by using Single‐Pot solid‐phase sample preparation (SP3). The whole IP‐SP3 approach can be completed in one day, which is considerably faster compared to the classical approach. No major quantitative differences are found between SP3 and FASP (filter‐aided sample preparation) or a longer incubation protocol. Taken together, the IP‐SP3 protocol is a fast and economical approach easily applicable for large‐scale protein interactome analysis.